We Are Soldiers Still : A Journey Back to the Battlefields of Vietnam - Moore, Harold G. and Galloway, Joseph L. (New York HarperPerennial, 2009)
To honor fallen comrades, a journalist and a soldier return to Vietnam battlefields more than 30 years later.
Include Illustrations and Index
Keywords: Moore, Harold G., -- 1922-2017 -- Travel -- Vietnam -- Galloway, Joseph L. -- Travel -- Vietnam -- Galloway, Joseph L